Influence of Food on the Bioavailability of an Enteric-Coated Tablet Formulation of Omeprazole 20 mg Under Repeated Dose Conditions - ABR Thomson; P Sinclair; A Matisko; E Rosen; T Andersson; B Olofsson (Canadian Journal of Gastroenterology)
The objective of this study was to investigate the influence of food on the bioavailability of omeprazole (20 mg) given as an enteric-coated tablet under repeated dose conditions. This open randomized crossover study consisted of three seven-day treatment periods, each separated by a drug-free period. During each treatment period an enteric-coated tablet of omeprazole was taken once daily either under fasting conditions, or immediately before or after a standardized breakfast. On the last day of each treatment period, blood samples for the determination of plasma omeprazole concentrations were collected at baseline and at predetermined intervals over the 24 h period following drug administration. Fifty-seven male and female subjects, aged 18 to 52 years, completed the study according to the protocol. No statistically significant differences were found when comparing either the before breakfast or after breakfast treatment regimens with the fasting regimen for the estimated mean area under the plasma concentration-time curve (AUC). The maximum plasma concentration was not found to differ significantly among any of the treatment regimens. However, the lower limit of the CI for the comparison of fasting/before breakfast was not contained within the limits of bioequivalence. The time to reach maximum plasma concentration was significantly different when fasting and after breakfast regimens were compared. Thus, under repeated dose conditions, food has no influence on the bioavailability (expressed as AUC) of omeprazole given as the enteric-coated tablet formulation.